Analysis of Lao's Interests toward Kumning-Viantiane High-Speed Railway Project with China - Emil Dariskiyah; Haryo Prasodjo; Hafid Adim Pradana (Universitas Muhammadiyah Malang, 2022)
This paper talks about an analysis of Lao's interest in working with China on the High-Speed Railway (HSR) project between Kumning, China, and Viantiane, Lao. Using a method called